Temporal dynamics modelling for aggression level of victims in disaster evacuation center - Mohd Shabli, Ahmad Hanis; Ab. Aziz, Azizi; Abu Bakar, Juliana Aida; Alwi, Asmidah; Che Pa, Noraziah (Universiti Teknikal Malaysia Melaka, 2017)
Natural disaster such as flood, earthquake, and typhoon poses a serious threat for humanity. However, post disaster is the hardest part to deal with. Assisting survivors who are looking for help always poses big challenges for volunteers to handle, especially when the number of victims is high.In this stage, emotional state of the victims is often unstable; and therefore, controlling them becomes a difficult task. This paper explained the idea of modelling individuals’ aggression levels in evacuation centers for floods (or any other natural disasters) victims. It described the development of a formal model that can be used as a base for building an intelligent agent or other types of software that can be helpful in training volunteers to handle victim’s aggressive.This will enhance the effectiveness of the volunteer work, thus improving the environment in the evacuation centers.